The effects of CACNA1C gene polymorphism on prefrontal cortex in both schizophrenia patients and healthy controls - Zhang, Zhifang; Wang, Yanyan; Zhang, Qiumei; Zhao, Wan; Chen, Xiongying; Zhai, Jinguo; Chen, Min; Du, Boqi; Deng, Xiaoxiang; Ji, Feng; Wang, Chuanyue; Xiang, Yutao; et al. (Schizophrenia research, 2019)
CACNA1C gene polymorphism rs2007044 has been reported to be associated with schizophrenia, but its underlying brain mechanism is not clear. First, we conducted an exploratory functional magnetic resonance imaging (fMRI) study using an N-BACK task and a Stroop task in 194 subjects (55 schizophrenia patients and 139 healthy controls). Our whole brain analysis found that the risk allele was associated with reduced activation of the left inferior frontal gyrus (IFG) during the Stroop task (cluster size = 390 voxels, P < 0.05 TFCE-FWE corrected; peak MNI coordinates: x = −57, y = −6, z = 30). We also conducted a functional near-infrared spectroscopy (fNIRS) study using the same Stroop task in an independent sample of 126 healthy controls to validate the fMRI finding. Our repeated-measures ANCOVA on the six channels (20, 27, 33, 34, 40 and 46) within the left IFG also found significant result. The polymorphism rs2007044 showed significant effect on the oxy-Hb data (F = 5.072, P = 0.026) and showed significant interaction effect with channels on the deoxy-Hb data (F = 2.841, P = 0.015). Taken together, results of this study suggested that rs2007044 could affect the activation of the left IFG, which was a possible brain mechanism underlying the association between CACNA1C gene polymorphism and schizophrenia.